CONTROLLING OF GREEN NANOCELLULOSE FIBER PROPERTIES PRODUCED BY CHEMO-MECHANICAL TREATMENT PROCESS VIA SEM, TEM, AFM AND IMAGE ANALYZER CHARACTERIZATION - Ireana Yusra, Abdul Fatah; Azizah, Endut; Hafizan, Juahir (2018)
Nanocellulose fibers were extracted from Oil Palm Empty Fruit Bunch (OPEFB) fibers by a chemo-mechanical treatment process. The aim of this study is to observe and investigate the morphological structure and fiber dimension characteristic of each stage in the nanocellulose production. The fiber structure characterization of the raw, purified pulps, extracted cellulose and nanocellulose fibers were controlled by observation and investigation under Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Atomic Force Microscopy (AFM) and Image Analyzer. The morphological observation illustrated that the isolation of nanocellulose fibers had greatly decreased from micron to nanoscale, up to 5-10 nm in diameter, and therefore suitable to be used as quality nano-reinforcement in the polymer matrix for a potential environmental green nanobiocomposites development